2019
DOI: 10.5603/ah.a2018.0016
|View full text |Cite
|
Sign up to set email alerts
|

The role of aldosterone in kidney diseases and hypertension. Is it worth using mineralocorticoid receptor antagonists in clinical practice?

Abstract: Aldosterone is a mineralocorticoid hormone which plays a pivotal role in water and electrolytes balance. Moreover, aldosterone exerts a deleterious influence on the cardiovascular system and kidneys. In this review, we wanted to show mechanisms of aldosterone related organ damage, the role of aldosterone in kidney diseases, hypertension and therapeutic benefits related with aldosterone receptors blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In a few studies in predialysis CKD patients, MRAs had been shown to reduce proteinuria and improve cardiovascular system function [8]. Cardioprotective effects of MRAs had been also shown in many reports in HD patients, but their influence on mortality is still a matter of debate [6]. Compared to HD patients, there were only a few reports of successful treatment with MRAs in PD patients with congestive heart failure (CHF).…”
Section: Discussionmentioning
confidence: 99%
“…In a few studies in predialysis CKD patients, MRAs had been shown to reduce proteinuria and improve cardiovascular system function [8]. Cardioprotective effects of MRAs had been also shown in many reports in HD patients, but their influence on mortality is still a matter of debate [6]. Compared to HD patients, there were only a few reports of successful treatment with MRAs in PD patients with congestive heart failure (CHF).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth remembering that the excess of aldosterone causes a weakening of the beneficial effect of ACE-Is on left ventricular (LV) hypertrophy (refractory LV hypertrophy) and an impairment of the nephrotective effect of ACE-I or ARB monotherapy [25]. The benefits of using the dual blockade have been found in a number of experimental studies.…”
Section: Dual Raas Blockade In Kidney Diseases Is There Still a Placmentioning
confidence: 99%